Can thermoregulatory response to heat stress be improved in lactating dairy cows? Insights from counter-current heat transfer systems impacting reproduction - Fernando LÓPEZ-GATIUS (The Journal of Reproduction and Development)
Climate change has caused heat stress (HS) to become an increasingly severe problem for high-producing dairy herds. Although cooling systems allow milk production to remain nearly constant throughout the year, fertility decreases during summer. Physiological counter-current heat transfer mechanisms maintaining brain/hypothalamic and reproductive functions in cattle are vulnerable to HS. In this study, I propose strategies to improve cooling systems, particularly in zones with the highest risk of increased body temperature, such as milking areas. In addition, heat transfer mechanisms to protect the brain–hypothalamus axis from hyperthermia must be considered when implementing measures to reduce HS-related problems.